2018
DOI: 10.1186/s12978-018-0481-z
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between raised body mass index and assisted reproductive treatment outcomes: a systematic review and meta-analysis of the evidence

Abstract: BackgroundPublic funding for fertility services within the United Kingdom is limited, and therefore, strict guidance exists regarding who can be offered treatment under the National Health Service (NHS). Body mass index (BMI) is a universal criteria adopted by both the public and private sector.This study addresses an important aspect of the impact of a raised BMI on fertility treatment outcomes. We standardise the analysis of the data by only including studies incorporating the WHO BMI criteria; the current r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 55 publications
(6 reference statements)
3
47
0
2
Order By: Relevance
“…According to the data in the present study, the total dose of recombinant FSH required for ovarian stimulation was significantly higher in overweight and obese women with BMI 25 kg/m 2 or over, corroborating previous data from studies with HCG injection (Maheshwari et al, 2007;Supramaniam et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…According to the data in the present study, the total dose of recombinant FSH required for ovarian stimulation was significantly higher in overweight and obese women with BMI 25 kg/m 2 or over, corroborating previous data from studies with HCG injection (Maheshwari et al, 2007;Supramaniam et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study support the hypothesis that the phenotypical characteristics of type 2 diabetes (chronic inflammation and insulin resistance) may increase the risk of a poor pregnancy outcome at all stages of fertilisation until the birth of the child. It is evident that being overweight has an adverse impact on fertility, pregnancy and the health of children born to women who are above the recommended BMI levels [33][34][35]. Our stratified analysis showed that women with type 2 diabetes who were classed as pre-obese and obese (BMI ≥25 kg/m 2 ) had a reduced chance of a liveborn child.…”
Section: Discussionmentioning
confidence: 87%
“…It is evident that being overweight has an adverse impact on fertility, pregnancy and the health of children born to women who are above the recommended BMI levels [ 33 35 ]. Our stratified analysis showed that women with type 2 diabetes who were classed as pre-obese and obese (BMI ≥25 kg/m 2 ) had a reduced chance of a live-born child.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in some studies (14)(15)(16), the obese group was included in the overweight group for analysis rather than the subdivision analysis. Though the mechanism of the negative effect of BMI on IVF outcome is unclear, the relationship may have a threshold effect on the CLBR by accumulative BMI.…”
Section: Discussionmentioning
confidence: 99%